Anatomical leg length discrepancy in children: Can it be accurately determined using 3-D motion capturing? - Böhm, Harald; Reinhold, Sophie M.; Dussa, Chakravarty U. (Gait & Posture, 2024)
Background: Leg length discrepancy (LLD) is common in youth and is cause by several conditions. Long leg X-rays is the gold standard technique of measuring LLD. It is highly accurate and reliable compared to clinical method, but expose the subject to radiation. Instrumented Gait Analysis (IGA) serves not only as a means to measure joint kinematics during gait but also as a valuable tool for assessing Leg Length Discrepancy (LLD) while standing. Research Question. The purpose of this study was to compare different methods of determining the LLD in paediatric population. We hypothesize that IGA using joint centres is more accurate and precise than the tape measurement. Methods: Thirty-one patients with mean age 12.3 (SD=2.4) years were retrospectively included in the study. Their LLD varied between 0 and 36 mm. Three methods for determining LLD were compared to radiography using Bland-Altman analysis: 1. Tape measurement, 2. IGA, summarizing the distance from the spina iliaca anterior superior to the medial malleolus marker via the medial knee condyle marker. 3. IGA, summarizing distances between ankle, knee, and hip joints centres where the latter is calculated with different equations. Results: The IGA joints method performed better than the tape measurement or IGA markers method. The equations of Davis calculating the hip joint centre had the highest accuracy with mean difference to radiography of 0.7 mm (SD=6.3). The simple Harrington method resulted in a slightly reduced accuracy but higher precision 0.9 mm (SD=6.2). The Harrington method with leg length as input was less accurate 1.0 mm (SD=6.7), but was still considerably better than the tape measurement 1.8 mm (SD=7.0) or IGA markers method 1.1 mm (SD=11.5). Significance. Determining LLD with IGA using the distances between ankle, knee and hip joints centres is a feasible method that can be applied in clinical practice to calculate LLD.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Gait analysis; Limb length difference; Orthopaedics; Radiography